Exploring dominant naming patterns in West Aceh and Nagan Raya: A linguistic and geographical analysis - Fahmi, Said Miftahul; Aziz, Zulfadli Abdul; Yusuf, Yunisrina Qismullah; Dewi, Cut (Universitas Islam Sultan Agung, 2025)
Naming patterns in Indonesia have shown the influence of geographical, social, and cultural factors on toponymy. Place naming in Aceh, a province in the country, has been based on the genesis and generic patterns that indicate specific objects, historical reasons, and word-forming elements. This study explores the dominant naming patterns found in the West Aceh and Nagan Raya regions by analyzing data sourced from regional databases, government archives, and the SIGAP (Sistem Informasi Gampong-Village Information System). A total of 131 place names from 29 villages were examined through literature review and document analysis as primary and secondary data sources. Thematic analysis, following Braun and Clarke’s (2006) framework, was employed to systematically identify recurring linguistic patterns. The results revealed nine dominant naming patterns in these regions, demonstrating a combination of different elements such as alue [aluə] ‘ditch’, blang [blaŋ] ‘rice field’, pasi [pasi] ‘beach’, suak [suaʔ] ‘estuary’, cöt [cət] ‘highland’, often combined with nouns or adjectives. This study illustrates how place names convey linguistic structures and geographical narratives that present Aceh's interconnection between language, landscape, and cultural identity. The findings contribute to broader discussions on the role of toponyms in preserving local knowledge and shaping regional identity.